The restoration of root filled teeth: a review of the clinical literature. (5th January 2021) - Bhuva, B.; Giovarruscio, M.; Rahim, N.; Bitter, K.; Mannocci, F.
Abstract: Clinicians often face dilemmas regarding the most appropriate way to restore a tooth following root canal treatment. Whilst there is established consensus on the importance of the ferrule effect on the predictable restoration of root filled teeth, other factors, such as residual tooth volume, tooth location, number of proximal contacts, timing of the definitive restoration and the presence of cracks, have been reported to influence restoration and tooth survival. The continued evolution of dental materials and techniques, combined with a trend towards more conservative endodontic‐restorative procedures, prompts re‐evaluation of the scientific literature. The aim of this literature review was to provide an updated overview of the existing clinical literature relating to the restoration of root filled teeth. An electronic literature search of the PubMed, Ovid (via EMBASE) and MEDLINE (via EMBASE) databases up to July 2020 was performed to identify articles that related the survival of root filled teeth and/or restoration type. The following and other terms were searched: restoration, crown, onlay, root canal, root filled, post, clinical, survival, success. Wherever possible, only clinical studies were selected for the literature review. Full texts of the identified articles were independently screened by two reviewers according to pre‐defined criteria. This review identifies the main clinical factors influencing the survival of teeth and restorations following root canal treatment in vivo and discusses the data related to specific restoration type on clinical survival.